High-fat diet consumption alters energy metabolism in the mouse hypothalamus - Lizarbe, Blanca; Cherix, Antoine; Duarte, João M. N.; Cardinaux, Jean-René; Gruetter, Rolf (International Journal of Obesity, 2019)
Background/Objectives High-fat diet consumption is known to trigger an inflammatory response in the hypothalamus, which has been characterized by an initial expression of pro-inflammatory genes followed by hypothalamic astrocytosis, microgliosis, and the appearance of neuronal injury markers. The specific effects of high-fat diet on hypothalamic energy metabolism and neurotransmission are however not yet known and have not been investigated before. Subjects/Methods We used 1 H and 13 C magnetic resonance spectroscopy (MRS) and immunofluorescence techniques to evaluate in vivo the consequences of high-saturated fat diet administration to mice, and explored the effects on hypothalamic metabolism in three mouse cohorts at different time points for up to 4 months. Results We found that high-fat diet increases significantly the hypothalamic levels of glucose ( P < 0.001), osmolytes ( P < 0.001), and neurotransmitters ( P < 0.05) from 2 months of diet, and alters the rates of metabolic ( P < 0.05) and neurotransmission fluxes ( P < 0.001), and the contribution of non-glycolytic substrates to hypothalamic metabolism ( P < 0.05) after 10 weeks of high-fat feeding. Conclusions/interpretation We report changes that reveal a high-fat diet-induced alteration of hypothalamic metabolism and neurotransmission that is quantifiable by 1 H and 13 C MRS in vivo, and present the first evidence of the extension of the inflammation pathology to a localized metabolic imbalance.